Effect of diurnal variation, CYP2B6 genotype and age on the pharmacokinetics of nevirapine in African children - Bienczak, Andrzej (J Antimicrob Chemother, 2017)
OBJECTIVES: To characterize the effects of CYP2B6 polymorphisms, diurnal variation and demographic factors on nevirapine pharmacokinetics in African children. METHODS: Non-linear mixed-effects modelling conducted in NONMEM 7.3 described nevirapine plasma concentration–time data from 414 children aged 0.3–15 years. RESULTS: Nevirapine pharmacokinetics was best described using a one-compartment disposition model with elimination through a well-stirred liver model accounting for a first-pass effect and transit-compartment absorption. Intrinsic clearance was affected by diurnal variation (characterized using a cosine function with peak amplitude 29% at 12 noon) and CYP2B6 metabolizer status [extensive metabolizer (EM) 516GG|983TT, reference; intermediate metabolizer (IM) 516GT|983TT or 516GG|983TC, 17% lower; slow metabolizer (SM) 516TT|983TT or 516GT|983TC, 50% lower; ultra-slow metabolizer (USM) 516GG|983CC, 68% lower]. Age was found to affect pre-hepatic bioavailability: 31.7% lower at birth and increasing exponentially. Median (90% CI) evening C(min) values in the different metabolizer groups were 5.01 (3.01–7.47), 6.55 (3.65–13.32), 11.59 (5.44–22.71) and 12.32 (12.32–27.25) mg/L, respectively. Evening C(min) values were <3 mg/L in 43% of EM weighing <6 kg and 26% of IM weighing <6 kg, while 73% of SM and 88% of USM in all weight-bands had evening C(min) values >8 mg/L. C(min) was not markedly affected by administration time, but was altered by unequal splitting of the daily dose. CONCLUSIONS: Diurnal variation does not greatly affect nevirapine exposure. However, when daily doses cannot be split equally, the larger dose should be given in the morning. To achieve homogeneous exposures, nevirapine doses for SM and USM should be reduced by 50%, and children weighing <6 kg with EM or IM metabolizer status should receive the same dose as children weighing 6–10 kg.